STUDENT SATISFACTION AS AN INDICATOR OF HIGHER EDUCATION QUALITY AT THE UNIVERSITY OF SHUMEN: STUDENT SATISFACTION AS AN INDICATOR OF HIGHER EDUCATION QUALITY AT THE UNIVERSITY OF SHUMEN - Todorova , Korneliya (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The article presents an empirical research in the University of Shumen aiming to assess students’ satisfaction with the educational activities as one of the indicators for estimation of education quality at the University. The purpose of this investigation is to examine the attitude of students towards studies at SU and to establish the level of students’ satisfaction with the quality of the educational process.